KNOWLEDGE, FAMILY SUPPORT, AND COMPLIANCE FOR PULMONARY TUBERCULOSIS MEDICATION AMONG PULMONARY TUBERCULOSIS PATIENTS - Zatihulwani, Eliza Zihni; Sari, Gevi Melliya; Rustanti, Elly; Putra, Kusuma Wijaya Ridi (Nurse and Holistic Care, 2023)
Background: Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis, which is an aerobic bacterium that can live mainly in the lungs or in various other organs of the body. According to the Health Profile of East Java Province in Pasuruan Regency in 2020, based on the achievement of TB treatment success rates as many as 18 districts/cities that have reached the target of treatment success of 91.510%. Objective: The purpose of this study was to determine the relationship between knowledge and family support with adherence to taking anti-tuberculosis drugs in TB patients in the Rembang Public Health Center, Pasuruan Regency. Methods: This study used a cross sectional research design with a sample of 27 respondents with pulmonary TB undergoing treatment at the Rembang Public Health Center. Data was collected using a questionnaire with an ordinal scale which was then analyzed using the Spearman Rank statistical test. Result: Data collection of knowledge with medication adherence with a correlation coefficient of .505 with a significant p-value = .000. Collecting data on family support with medication adherence with a correlation coefficient of .487 with a significant p-value = .000. Conclusion: It was concluded that there was a relationship between knowledge and family support with adherence to taking anti-tuberculosis drugs. The higher a person's education and family support, the more quickly they receive and understand information so that the knowledge and support from their family is also higher.